Analysis of Quality Control of Fabric Products Using Statistical Quality Control (SQC) Methods and Failure Mode and Effect Analysis (FMEA) - Al Habri, Muhammad Anjab; Donoriyanto, Dwi Sukma (Newinera Publisher, 2025)
Companies in the industrial world, both manufacturing and service industries, are required to face market competition in order to compete and survive. One thing that companies need to pay attention to is the quality of the products produced. Good product quality will make consumers like the product. Therefore, improving product quality must be considered by the company. One of the companies that produces fabric, namely PT. XYZ, has a problem of not knowing the level of quality of the fabric produced, so this study aims to determine the quality of the product and provide suggestions for improvement to the company. There are defects in fabric production, namely double weft with a percentage of 27.7%, loose weft 26.7%, broken warp 24.5% and thick weft 21.2%. Improvement proposals are given to the highest percentage of defects, namely double weft with the following proposals: Carrying out machine maintenance and replacing the new gun eye so that the gun eye is not blunt, replacing the roller on the worn warping machine with a new roller, providing comprehensive and intensive training to workers on how to use the machine effectively and correctly. It is hoped that this research can help the company improve the quality of the fabric products produced.